The Impact of Productivity Increasing in Indonesian Maritim Sector: General Equilibrium Analysis - Widyastutik Widyastutik (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
The increase in productivity in the maritime sector will realize the maritime sector as a prime mover. This study aims to analyze the impact of the maritime sector productivity improvement on the performance of the economy. This research simulates increased productivity in the maritime sector (consisting of the fisheries, oil, gas sub-sector and marine transport services sector) using the Global Trade Analysis Project (GTAP) version 8. Simulation analysis showed an increase in productivity in the maritime sector has a positive impact on welfare, real GDP, and trade balance of Indonesia. However, the impact of the increase in productivity is not followed by an increase in output in all sectors. This indicates that if the increase in productivity occurs only in the maritime sector alone without being followed by an increase in productivity in other sectors, the sectoral performance is not optimal.DOI: 10.15408/sjie.v5i2.3403